Digital transit ports for the illicit trade in antiquities: the case of the 'Afghan Genizah'. - Palombo, Cecilia; Yates, Donna (Digital Scholarship in the Humanities, 2023)
In this article, we present the idea of a digital transit port, an online space that illicit cultural objects pass through in digital format while on a pathway to public legitimization. These virtual transit ports connect virtual illicit and illegally trafficked cultural objects with virtual consumers under the aegis of promoting access and preservation, while simultaneously normalizing the presence of these objects in market and academic spaces. Digital transit ports, then, make virtual versions of illicit cultural objects openly consumable, much like physical transit ports launder physical cultural objects. They may also legitimize use of the physical objects, infringing on legislative efforts at curbing the illicit trade. To explore the idea of the digital transit port, we will consider the case of the so-called 'Afghan Genizah' collection, a disarticulated group of historical documents from northern Afghanistan that have appeared on the international market most likely after being looted and trafficked illicitly outside their country of origin.